Panama : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
Panama's per capita GDP has doubled, driven by a steady rise in public and private investment underpinned by a stable macroeconomic environment and prudent policies. Easy credit and fiscal conditions should continue to support public and private consumption. Further fiscal restraint through better tax administration and expenditure management and enhanced buffers would help cope with adverse spillovers. There is progress in implementing financial sector assessment program (FSAP) recommendations, though there is a need to upgrade financial sector supervision. Improvements in competitiveness and recent education reforms should help sustain growth over the medium term.